2001
DOI: 10.1080/109158101317097700
|View full text |Cite
|
Sign up to set email alerts
|

Two-Generation Reproduction Study and Immunotoxicity Screen in Rats Dosed with Phenol via the Drinking Water

Abstract: This study evaluated the potential reproductive toxicity of phenol in a rat two-generation reproduction study, which included additional study endpoints, such as sperm count and motility, developmental landmarks, histological evaluation of suspect target organs (liver, kidneys, spleen, and thymus), weanling reproductive organ weights, and an immunotoxicity screening plaque assay. Phenol was administered to 30 Sprague-Dawley rats/sex/group in the drinking water at concentrations of 0, 200, 1000, or 5000 ppm. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 10 publications
1
36
0
3
Order By: Relevance
“…In line with these results, similarly, previous studies have demonstrated the immunological alterations on the splenic-forming cells and corresponding circulating antibody levels (Hsieh et al 1992) in the CD-1 mice. In contrast, no spleen toxicity was observed in the study of Ryan et al (2001) on the Sprague–Dawley rats. This dissimilarity may be associated with possible interspecies and inter strains differences between rats and mice for this endpoint.…”
Section: Discussionmentioning
confidence: 79%
“…In line with these results, similarly, previous studies have demonstrated the immunological alterations on the splenic-forming cells and corresponding circulating antibody levels (Hsieh et al 1992) in the CD-1 mice. In contrast, no spleen toxicity was observed in the study of Ryan et al (2001) on the Sprague–Dawley rats. This dissimilarity may be associated with possible interspecies and inter strains differences between rats and mice for this endpoint.…”
Section: Discussionmentioning
confidence: 79%
“…The potential reproductive toxicity of phenol was investigated in a two-generation reproductive study in rats [13]. In this study phenol was administered via the drinking water at doses of 0–5,000 parts per million for a period of 10 weeks before and during mating and gestation for two consecutive generations of rats.…”
Section: Composition Of Liquid Gh Formulations For Injectionmentioning
confidence: 99%
“…For example, Ryan et al [16] administered phenol in the drinking water and observed reproductive effects (e.g., reduced survival of F 1 pups) at the highest dose level (379.5 mg/kg), a dose that was approximately six times greater than the dose that produced similar effects in a gavage study [14]. A contrast is evident in the toxic effects of phenol when administered as a bolus compared to similar doses administered throughout the day.…”
Section: Studies Relevant For Mammalian Trv Development For Ingestionmentioning
confidence: 99%